Mirzo Bedil's Personality And Ontological Views - Tavmurodov Jamshid (Open Academia, 2025)
This article presents an analysis of Bedil’s socio-philosophical views, his life journey, literary works, and profound philosophical reflections. It further explores how, in his teachings on existence, Bedil addressed the ontological, religious, and secular issues of his time, creatively engaging with gnoseological and axiological problems through incisive and often ironic expression
Keywords: Sufism; intuition; existence